Analisis Tingkat Kontaminasi Bakteri Escherichia Coli pada Air Sumur Gali pada Tahap Sebelum dan Sesudah Perebusan - Duwi Yuliana Arini; Wiwit Probowati; Widaninggar Rahma Putri (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Water was from a native natural fountain that is became vital for human life, particularly as source of drinking water also for things household needs. However, the use of dug well water is highly susceptible to bacteriological contamination. Contamination of drinking water with Escherichia coli is a leading cause of gastrointestinal infections and diarrhea. This reseach was purposelly to identifying the  exsist of E. coli in dug well water also established the impact as well range from septic tank and the effectiveness of the boiling process. The method was using a quantitative approach using an experimental design. The samples including of 14 dug wells gap less than 10 meters also more than 10 meters from a septic tank, with treatments before and after boiling. Laboratory analysis were including use the MPN (Most Probable Number) method thru a presumptive test (Lactose Broth), a confirmatory test (Brilliant Green Lactose Bile Broth), and an identification test (Eosin Methylene Blue Agar). Data were statistically analyzing use technique of Shapiro-Wilk normality test also the non-parametric Wilcoxon signed-rank test. The yields demonstrated that physical distance was not significantly correlated with bacterial contamination levels. The Wilcoxon test revealed a significant and notable difference in bacterial contamination levels before and after boiling, indicating that the boiling process effectively reduced biological contamination in the water. After boiling, 7 samples met drinking water standards (0 MPN/100 ml), while the other 7 samples were still found to contain bacteria due to issues with equipment sterilization or procedure.